Corrective feedback and learner uptake in selected Iranian EFL classrooms - Pouriran, Yassamin (2014)
Considering the well-proven benefits of participation in communicative interactions and the incorporation of focus on form instruction into communicative classes, this study investigates how frequently reactive focus on form is employed in communicatively oriented English as Foreign Language classes (EFL). Despite the extensive number of empirical studies on the type, rate, and effectiveness of planned reactive focus on form, incidental focus on form in general has not enjoyed this much attention in EFL contexts, and an investigation of their frequency and effectiveness is almost missing from the literature on focus on form studies. In this concern, the present study expands current accounts of focus on form instruction by investigating the role of reactive Focus on Form Episodes (FFEs) in raising students’ awareness and noticing of linguistic items in EFL settings. This study investigates the connection between teachers’ incidental focus on form: namely, reactive focus on form and learners’ uptake and immediate repair of errors in communicative EFL classrooms for adults. Moreover, the study examines the linguistic focus of FFEs, i.e., vocabulary, grammar and pronunciation. The data is drawn from transcripts of oral corrective feedback moves of 10 audio and video-recorded classrooms at intermediate level totaling 60 hours. Ten teachers, experienced and less-experienced,participated in this study. This study is a descriptive type which employs qualitative data collection procedures methods, quantitative data are also collected to complement the qualitative one. The results reveal a significant difference in the ratio of uptake following certain corrective feedback types. In addition, some new types of incidental focus on form have been discovered in EFL classrooms which are named as: integrated feedback and ancillary feedback by the researcher. There is also a meaningful difference of experienced and less-experienced teachers’ beliefs in using different types of corrective feedback in their classes. The results show that experienced teachers use incidental focus on form techniques more frequently than their counterparts. Furthermore,teachers’ beliefs and their self-reported practices were explored through a questionnaire. This study supports the notion that conducting activities which can integrate a focus on form into L2 communicative activities can contribute to learning a foreign language in terms of both accuracy and fluency. Possible reasons are discussed from different aspects of learners’ age, their motivation, and instructional settings. This study finally aims to focus on the EFL teachers’ awareness to make accurate decisions on integrating different types of incidental focus on form practices with communicative methodology.